Bis(2-amino-3H-benzothiazolium) bis(7-oxabicyclo[2.2.1]heptane-2,3-dicarboxylato)cobaltate(II) hexahydrate - Na Wang; Qiu-Yue Lin; Jie Feng; Shi-Kun Li; Jun-Jun Zhao (Acta Crystallographica Section E, 2010)
In the crystal structure of the title salt, (C7H7N2S)2[Co(C8H8O5)2]·6H2O, the heterocyclic N atom of the 2-aminobenzothiazole molecule is protonated. The CoII atom is situated on an inversion centre and exhibits a slightly distorted octahedral CoO6 coordination defined by the bridging O atoms of the bicycloheptane unit and four carboxylate O atoms of two symmetry-related and fully deprotonated ligands. The crystal packing is stabilized by N—H...O hydrogen bonds between the cations and anions and by O—H...O hydrogen bonds including the crystal water molecules.